MENJELAJAH ALAM SEBUAH RENUNGAN FILOSOFIS TENTANG SAINS - Surjani Wonorahardjo (Studia Philosophica et Theologica, 2003)
The achievement of modern science discovered many aspects of the nature that give the ability to reflect deeply to the root of our existence. Dynamics plays a crucial role in micro scale of object, and according to the Heisenberg principle, the exactness of the small object can be expressed only by probabilities. The nature of small objects can also be the main constituent of the bigger object in nature. This makes the stability of bigger objects to a certain extent depends on the microscale´s nature. Along with the progress in science, philosophy shitfts the direction of its topics. Subjectivity comes forwards but the objectivity is not put aside. These two alternate during the time as the consciousness plays ist role. The beauty of nature is then seen more and more clearly, in „order“ as well as in „chaos“. The micro nature is the new subject in science, and fenomenology in post modernism is also the field of today´s philosophy.